IMPROVING STUDENTS’ VOCABULARY BY USING TALULAR - Wulan Aprilia; Endang Susilawati; Syarif Husin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The aim of this research was to improve students’ vocabulary byusing TALULAR. This research was Classroom Action Research(CAR) that implemented in one cycle by using two classroomactivities; Jumble Words and Jumble Sentences. The participant forthis research was the fifth-grade students at SD Negeri 67Singkawang in the academic year 2021/2022 with 10 students as the totalnumber. To improve the fifth-grade students’ vocabulary, theresearcher decided to use TALULAR as the vocabulary learningresource. TALULAR is an acronym that stands for Teaching andLearning Using Locally Available Resources, which means theprocess of teaching-learning using surrounding things or persons asthe learning resources to correlate the materials. In conducting thisresearch, the researcher collected the data through the interview andobservation by using interview questions and field notes. Basedon the research findings, showed that students had improved theirvocabulary toward sources used in teaching and learning.TALULAR provided the aspect of familiarity and authenticitythrough real objects and pictures, which helped students to know theterms and its meaning. The researcher implemented TALULARthrough two classroom activities; jumble word and jumble sentence,where students learned things related to their daily activity, whichwas farming. As the result, all of the students were able to know theEnglish terms of farming activity. Therefore, it can be concluded thatTALULAR is able to improve students’ vocabulary. In another word,the action hypothesis is accepted.